Efektivitas Penggunaan Jasa Influencer dalam Meningkatkan Penjualan Produk Seruit Tampah Mengan Geh Lampung - Estelee Elora Akbar; Ana Santika (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study was conducted to examine the effectiveness of the use of influencer services by business actors seruit tampah mengan geh in increasing sales of their products. The results of the study found that the use of influencer services can be categorized as effective and efficient, this is evidenced by the increase in product brand awareness, increased consumer trust through honest influencer reviews, targeted audiences and more creative content results that attract the interest of viewers of the content produced.